Global Programmed Switch in Neural Daughter Cell Proliferation Mode Triggered by a Temporal Gene Cascade. - Baumgardt, M.; Karlsson, D.; Salmani, B.Y.; Bivik, C.; MacDonald, R.B.; Gunnar, E.; Thor, S. (Developmental Cell, 2014)
During central nervous system (CNS) development, progenitors typically divide asymmetrically, renewing themselves while budding off daughter cells with more limited proliferative potential. Variation in daughter cell proliferation has a profound impact on CNS development and evolution, but the underlying mechanisms remain poorly understood. We find that Drosophila embryonic neural progenitors (neuroblasts) undergo a programmed daughter proliferation mode switch, from generating daughters that divide once (type I) to generating neurons directly (type 0). This typeI>0 switch is triggered by activation of Dacapo (mammalian p21(CIP1)/p27(KIP1)/p57(Kip2)) expression in neuroblasts. In the thoracic region, Dacapo expression is activated by the temporal cascade (castor) and the Hox gene Antennapedia. In addition, castor, Antennapedia, and the late temporal gene grainyhead act combinatorially to control the precise timing of neuroblast cell-cycle exit by repressing Cyclin E and E2f. This reveals a logical principle underlying progenitor and daughter cell proliferation control in the Drosophila CNS.